Model Program Unggulan Peningkatan Prestasi Akademik dan Non-akademik Madrasah Aliyah di Daerah Pandeglang, Banten - Hernanda, Nabila; Alifah , Nasywa Nur; Nurazizah, Siti; Hojijah, Siti; Herliyanti, Adinda; Usman, Usman (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2025)
This study aims to examine the excellent program model applied at Madrasah Aliyah Swasta Ibad Ar Rahman, Pandeglang, in improving students' academic and non-academic achievements. The method used is a qualitative approach with data collection techniques in the form of interviews, observation, and documentation with data sources obtained from the subject of the research site. The results showed that the madrasah successfully integrated academic and non-academic guidance programs, extracurricular activities, strategic partnerships, and adequate supporting facilities. The implementation of this excellent program has proven effective in shaping student character, improving achievement, and producing highly competitive graduates. These findings indicate the importance of adaptive, relevant, and sustainable program development as a strategy to improve the quality of education.